“Skills for Resilience in Farming”; an evidence-based, theory driven educational intervention to increase mental health literacy and help-seeking intentions among Irish farmers - Siobhán O’Connor; Sandra M. Malone; Joseph Firnhaber; Sinéad O’Keeffe; John McNamara; Anna Donnla O’Hagan (PLoS ONE, 2025)
While mental health literacy is an important component to successful help-seeking, rural populations often face gaps in both knowledge and service provision. Informed by the Theory of Planned Behaviour and Self-Efficacy Theory, we designed the ‘Skills for Resilience’ as a brief, once-off, community-based educational intervention to increase Irish farmers’ mental health literacy and help-seeking intentions. We adopted a quasi-experimental between (group: intervention and control) and within-group design (time: baseline [T1], immediately post-intervention [T2], and ≥ 1 month post-intervention [T3]). A total of 72 participants (intervention n = 37; control n = 35) were recruited from knowledge-sharing discussion groups. Although recruitment was also open to women, all discussion groups consisted of men. A trained facilitator delivered a discussion lasting between 30 and 90 minutes. Five intervention participants also participated in a qualitative interview after T3. Our results identified intervention participants’ mental health literacy increased significantly at T2 and T3 compared to T1, but did not increase between T2 and T3. Mental health literacy was also significantly greater in the intervention group compared to the control group at T2 and T3. Help-seeking intentions and self-efficacy in seeking mental healthcare also increased significantly at T2 compared to T1, but did not increase between T1 and T3 or T2 and T3. There were no significant changes in outcome measures for the control group at any time point. Through reflexive thematic analysis we identified that the intervention also addressed stigma against mental health (Theme 1) and provided important resources for participants and their community’s present and future coping (Theme 2). At T3, 100% of participants enjoyed the discussion and would recommend the intervention to other farmers. This intervention provides a successful example of integrating the Theory of Planned Behaviour and Self-Efficacy Theory to improve mental health literacy in farmers using a brief, educational intervention.